Protocolo de atención de enfermería y su relación con la prevención de complicaciones en el embarazo adolescente, Hospital General IESS Babahoyo, octubre 2024 – mayo 2025. - Cercado Villasagua, Eugenia Lisseth (2024)
The present work entitled: Nursing care protocol and its relationship with the prevention of complications in adolescent pregnancy, IESS Babahoyo General Hospital, October 2024 - May 2025, aims to analyze the influence of the nursing care protocol with the prevention of complications in adolescent pregnancy, in the referred hospital in the determined period, considering that pregnancies in the adolescent stage are very frequent and for state agencies they are considered a social health problem, its causes are diverse and the consequences range from the marginalization of adolescents to problems of psychological aggression, reaching the point of excluding them from their family environment, leaving them defenseless, vulnerable and in situations of serious risk for themselves and their descendants. The methodology used in the present study is longitudinal and descriptive, with a mixed approach. It was analyzed how nursing protocols influence the prevention of complications in teenage pregnancies, a documentary modality by collecting information from texts, magazines and scientific and field articles at the time of conducting surveys, interviews and observation sheets, having as a sample the 132 pregnant adolescents attended and the professionals of the IESS Babahoyo General Hospital (October 2024 - May 2025), obtaining as results that the nursing care protocol is closely related to the prevention of complications in teenage pregnancy, guaranteeing the health of the pregnant woman and the product.